MODIFICATION OF THE STANDARD 7-DAY OVSYNCH PROTOCOL TO INCREASE THE LUTEOLYTIC AND SYNCHRONIZATION RISKS IN DAIRY COWS - Atanasov Branko, Adamov Nikola , Celeska Irena , Ilievska Ksenija, Angjelovski Branko, Trbogazov Zvonko, Davkov Filip , Dovenski Toni, Opsomer Geert, Stevenson Jeffrey (My University, 2020)
We hypothesized that a single dose of PGF2α belatedly injected on day 8 after GnRH-1 in cows receiving a 7-day Ovsynch-56 protocol (GnRH – 7 days – PGF2α – 56h – GnRH – 16h – timed AI) will increase the proportion of cows with complete luteolysis. At day 35±3 postpartum, 70 lactating Holstein cows from one herd were scored for body condition and pre-synchronized with PGF2α and GnRH (3 days apart) and 7 days later submitted to an Ovsynch-56 protocol for first AI after random assignment to two treatments: (1) OV-7 (n=35) with an injection of PGF2α either on day 7; or (2) OV-8 (n=35) on day 8 after G1, respectively. Blood was collected before the first PGF2α, at day 7 and day 8 in OV-7 and OV-8, respectively, at AI and at 7 days after AI to assess progesterone concentration. Ten cows were classified as acyclic and were excluded from the analysis resulting in 60 cows (OV-8, n=27; OV-7, n=33). In total, more (P=0.01) OV-8 cows and more (P=0.04) primiparous OV-8 cows had complete luteolysis compared with their OV-7 herd mates. In addition, more (P=0.008) OV-8 cows with BCS<2.75 had complete luteolysis compared with their OV-7 herd mates, whereas no difference was observed between treatments among cows with BCS ≥2.75. In conclusion, delaying the application of PGF2α by 1 day reduced the percentage of primiparous cows and cows with poorer BCS having incomplete luteal regression at the time of AI.
Keywords: luteolysis, synchronization risk, Ovsynch, dairy cows, BCS